Weakening of springtime Arctic ozone depletion with climate change - Friedel, Marina; id_orcid:0 000-0001-7739-4691; Chiodo, Gabriel; id_orcid:0 000-0002-8079-6314; Peter, Thomas; id_orcid:0 000-0002-7218-7156 (Copernicus, 2023)
Arctic ozone is subject to large interannual variability, and severe ozone minima can occur through chemical ozone depletion and dynamical variability. Such Arctic ozone minima have been shown to bear a great societal relevance due to their impacts on health and climate. Following the success of the Montreal Protocol, ozone depleting substances (ODSs) in the stratosphere are declining, implying an expected weakening of chemical ozone destruction. However, continuing greenhouse gas (GHG) emissions cool the stratosphere, which might lead to an enhanced formation of polar stratospheric clouds (PSCs) and thus more efficient chemical depletion of ozone. Due to these opposing processes, there is currently no consensus on the fate of Arctic ozone minima in future climate. Here, we investigate the future evolution of Arctic ozone minima over the 21st century under different emission pathways in simulations conducted for the Chemistry-Climate Model Initiative (CCMI), CCMI-1 and CCMI-2022, and constrain these projections based on the models’ skill in reproducing present-day Arctic ozone variability. We find a large model discrepancy in the magnitude of ozone minima under present-day climate, caused by biases in the underlying model climatology. Models that simulate large ozone minima in present-day climate generally have a cold bias, and consequently large concentrations of active chlorine species (ClOx); these are the models that project the largest decline in the magnitude of ozone minima in the future. Conversely, models simulating weak Arctic ozone minima under present-day conditions generally have a warm bias and small ClOx concentrations; these are models with the smallest sensitivity of ozone minima to changes in ODS and GHG emissions. Consequently, inter-model spread in the magnitude of springtime Arctic ozone minima is projected to decline in the future. Through comparison with reanalysis, we identify the most realistic models. These models show a weakening in stratospheric ozone minima of about 1 DU/decade and ...